Analysis of luminescent coupling effects in n series‐connected multijunction solar cells. Issue 4 (29th February 2016) - Mazouchi, Mojgan; Jia, Jieyang; Huo, Yijie; Miao, Yu; Kang, Yangsen; Chen, Yusi; Harris, James S.; Dutta, Mitra
Abstract : In this work, the luminescent coupling (LC) effects on photocurrent‐matched and photocurrent‐mismatched multijunction solar cells are investigated from fundamental physical theories and modeled by spice circuit simulations. It is demonstrated that the voltage increase of a photocurrent‐matched cell is constant in the voltage range from maximum power point to open‐circuit point, and this increase depends on the number of junctions and LC efficiency. Through the LC effects, it is shown that at the operation point of a photocurrent‐matched double‐junction (2J) cell, the photons from radiative recombination (which is the dominated recombination mechanism) of the top junction, is not wasted, but instead couples downward to the bottom junction, doubles the second junction's recombination current density, and leads to a significant voltage increase of k T / q   ln ( 2 )  = 17.8 mV. The same physics extended to a photocurrent‐matched triple‐junction (3J) cell with an increase of k T / q   ln ( 2 × 3 )  = 46 mV and n‐junction cell with an increase of k T / q   ln ( n ! ) . Furthermore, it is shown that the theoretical prediction matches the circuit simulations exactly, and this tens of millivolts enhancement in voltage increases with increasing the number of junctions, consequently leads to a greater improvement in cell performance.